2002
DOI: 10.1073/pnas.032664299
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent evolution of DNA-binding motifs in the Drosophila centromeric histone

Abstract: All eukaryotes contain centromere-specific histone H3 variants (CenH3s), which replace H3 in centromeric chromatin. We have previously documented the adaptive evolution of the Drosophila CenH3 (Cid) in comparisons of Drosophila melanogaster and Drosophila simulans, a divergence of Ϸ2.5 million years. We have proposed that rapidly changing centromeric DNA may be driving CenH3's altered DNA-binding specificity. Here, we compare Cid sequences from a phylogenetically broader group of Drosophila species to suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
115
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 41 publications
(51 reference statements)
10
115
0
Order By: Relevance
“…The discovery that HMfA had much lower affinity than HMfB for the clone 20 sequence (27) added strong support to this idea, and the widely distributed and conserved presence of histone variants in many Eukaryotes (42) is also consistent with this concept. It is already well established that incorporation of the CENP-A family of histone H3 variants results in nucleosomes that assemble specifically at the centromere (11)(12)(13)(14)(15)(16)(17). Although unique functions have not yet been assigned to these nucleosomes, this positioning is entirely consistent with the demonstration here that very similar histone fold dimers can assemble into tetramers with structures so different that they have different DNA affinities.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The discovery that HMfA had much lower affinity than HMfB for the clone 20 sequence (27) added strong support to this idea, and the widely distributed and conserved presence of histone variants in many Eukaryotes (42) is also consistent with this concept. It is already well established that incorporation of the CENP-A family of histone H3 variants results in nucleosomes that assemble specifically at the centromere (11)(12)(13)(14)(15)(16)(17). Although unique functions have not yet been assigned to these nucleosomes, this positioning is entirely consistent with the demonstration here that very similar histone fold dimers can assemble into tetramers with structures so different that they have different DNA affinities.…”
Section: Discussionsupporting
confidence: 75%
“…Nucleosomes containing the histone H3 variant alternatively designated CENP-A, CSE4p, CID, HCP-3, or SpCENP-A (11) assemble only at centromeric DNA. Mutagenesis and domain-swap experiments have revealed that this localization is similarly dependent on a difference at the histone dimer:dimer interface in (CENPϪAϩH4) 2 and (CSE4pϩH4) 2 versus (H3ϩH4) 2 tetramers (12)(13)(14)(15)(16)(17). Based on their crystal structures, nucleosomes assembled with histones from different species or histone variants do exhibit higher order structural differences, again most notably at the sites of histone dimer:dimer interactions (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Nonetheless, many of the functional components of meiosis and recombination evolve rapidly (e.g., Malik et al 2002;Anderson et al 2009;Myers et al 2010). One explanation for this rapid evolution is that meiosis and gametogenesis offer a number of opportunities for genomic conflict within an individual, generating a pattern of antagonistic coevolution between selfish gametic drivers and suppressors of meiotic drive (see Burt and Trivers 2006, for a broad overview).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that this coevolution will ultimately lead to incompatibilities in the form of inviability or sterility in hybrids from populations with divergent centromere machinery (Henikoff et al, 2001a). Corroboration for this 'centromere-drive' model appears to exist among Drosophila, where the main centromere-binding protein, Cid (centromere identifier), has been demonstrated to have undergone strong and recurrent adaptive evolution, presumably in response to changes in centromeric satellite sequences (Malik and Henikoff, 2001;Malik et al, 2002). However, the centromere-drive mechanism, which has the potential to act as a universal cause of divergence in almost any incipient eukaryotic species, has yet to be demonstrated to have any direct influence on naturally occurring patterns of reproductive isolation.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila the critical centromere-specific histone gene cid has been sequenced from a number of species and is thought to have been evolving adaptively in numerous lineages for at least 25 million years (Malik et al, 2002). A dramatic recent round of selection has driven the adaptive divergence of this gene in the sister taxa Drosophila simulans and D. melanogaster (Malik and Henikoff, 2001).…”
Section: Introductionmentioning
confidence: 99%